Genetic Diversity of Native Provenance and Plantation Populations of Pinus sylvestris var. mongolica Based on SSR Markers and Morphological Traits - Mingyu Yin; Bo Wu; Yingjun Pang; Tana Wuyun (Ecology and Evolution)
ABSTRACT Pinus sylvestris var. mongolica plays a crucial role in the ecological restoration and industrial raw material production of arid and semiarid regions in northern China. The widespread degradation of its near‐mature plantation (over 30 years) is a significant concern, having been a topic of interest in recent decades. In this study, the genetic diversity and population genetic structure were assessed using 12 simple sequence repeat (SSR) markers within 11 native provenance populations and eight plantation populations. Additionally, variations in eight morphological traits of their offspring were evaluated at three sites in northern China. The results revealed high genetic diversity and weak genetic differentiation among the native provenance populations. The mean number of alleles (Na), allelic richness (Ar), expected heterozygosity (He), and Shannon–Wiener diversity index (I) were 5.492, 4.679, 0.550, and 1.120, respectively, and the genetic differentiation coefficient (FST) was 0.022. Significant population effects of tree height and height to live crown base (HCB), as well as interactions of population with site and block within site, were observed in tree height, HCB, stem diameter at breast height (DBH), stem volume (VOL), crown shape (CS), and disease grade (DG). The genetic diversity parameters based on SSR markers and breeding values of tree height, DBH, HCB, VOL, and stem form (SF) of plantation populations were found to be lower than those of native provenance populations. Significant positive correlations were identified between the mean effective number of alleles per locus (Ne) and VOL as well as He and crown width (CW). Furthermore, the maximum temperature of the warmest month (BIO5) and the silt content (T_SILT) were identified as significant factors influencing genetic diversity parameters and morphological variation, respectively. The findings provide scientific support for the reduction of plantation degradation, the effective restoration, and the sustainable management of forests for this species.